Entrepreneurial management - Bhargava, Shivganesh, 1959- (Los Angeles : Response Books, 2008)
In Indian context.
1. Entrepreneurial Management: Emergence of a New Field -- Entrepreneurship: An Emerging Interdisciplinary Field of Study / S. Bhargava -- 2. Network of Entrepreneurship and Economic Development (NEED) A Facilitating Organization of Micro-enterprise and Self Help Groups / Shailendra Singh -- 3. A Resourcebased Perspective to International Entrepreneurship / Deeksha A. Singh -- 4. Developing Entrepreneurial Workforce for Sustainable Growth of the Small-Scale Sector / V.P. Wani -- 5. Does Human Resource Factor Matter in Achieving Energy Efficiency in Small Industry Clusters? An Empirical Study / N. Nagesha -- 6. Effect of Market Turbulence and Market Focus on the Firms Performance in Small- and -Medium Scale Manufacturing Firms / Sanjay S. Gaur and Hari Vasudevan -- 7. Student Expectations of Entrepreneurs: A Survey / Francis Jose -- 8. Examining the Relationship of Sociocultural Factors and Entrepreneurial Propensity among Professional Students / Kailash B.L. Srivastava -- 9. Motivational Factors Influencing Industrial Entrepreneurship in Rajasthan / R. Raghunathan -- 10. Psychosocial Perceptional Differences: An Empirical Exploratory Study on Indian Food Processing Women Entrepreneurs / R. Ganesan, R.P. Pradhan and R.C. Maheshwari -- 11. A Study of Life-situation Antecedence, Personality and Motivational Patterns of Small-Scale Women Entrepreneurs / T.J. Kamalanabhan and V. Vijaya -- 12. Women Entrepreneurship: A Case of Micro-Enterprises / N. Manimekalai and Mohammed Abdullah -- 13. Strategic Role of Engineering Institutions for Entrepreneurship Development in India / Dinesh Khanduja and Rajeev Khanduja -- 14. Building Entrepreneurial Society in India through Business Incubation / M.K. Sridhar and M.V. Ravikumar.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Entrepreneurship; Management; Entrepreneurship; Entrepreneuriat; Gestion; entrepreneurs; management; BUSINESS & ECONOMICS -- Entrepreneurship; Entrepreneurship; Management